2007
DOI: 10.2741/2441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of androgen-deprivation therapy on the immune system: implications for combination therapy of prostate cancer

Abstract: Prostate cancer is the most common non-cutaneous malignancy in American men. Standard therapeutic strategies for systemic disease include androgen-deprivation therapy (ADT) and chemotherapy, both of which are palliative. However, there is a growing interest in the use of immunotherapy for prostate cancer. Evidence suggests that ADT may 1) enhance lymphopoiesis and thus potentially improve immune responses to vaccine, 2) renew thymopoiesis and thus reverse age-induced thymic involution, 3) augment B-cell develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 92 publications
2
91
0
2
Order By: Relevance
“…As reviewed by Aragon-Ching et al (32), phase I and phase II trials indicated that androgen ablation may boost immune responses elicited by DCs, allogeneic prostate cancer cell lysate, or GM-CSF-secreting tumor cell-based vaccines (88). Arlen et al (89) were the first to conduct a randomized study evaluating the use of vaccine alone versus concomitant vaccine plus weekly administration of docetaxel and steroids, with the end points of monitoring immune responses in 28 patients bearing a metastatic, androgen-resistant prostate cancer.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed by Aragon-Ching et al (32), phase I and phase II trials indicated that androgen ablation may boost immune responses elicited by DCs, allogeneic prostate cancer cell lysate, or GM-CSF-secreting tumor cell-based vaccines (88). Arlen et al (89) were the first to conduct a randomized study evaluating the use of vaccine alone versus concomitant vaccine plus weekly administration of docetaxel and steroids, with the end points of monitoring immune responses in 28 patients bearing a metastatic, androgen-resistant prostate cancer.…”
Section: Figurementioning
confidence: 99%
“…The influence of androgens on lymphocyte development and activation has been reviewed (32). Experimental data indicate that androgen deprivation increases the number of naive T cells exported from the thymus and may therefore contribute to broadening the repertoire of T cell immunity, leading to effective antitumor immune responses and breaking of tumor-induced tolerance (33,34).…”
Section: Immunostimulatory Side Effects Of Anticancer Drugsmentioning
confidence: 99%
“…Following a phase I trial of Adv-tk in men with locally recurrent prostate cancer showing its safety and trial data demonstrating a significant increase in PSA doubling time (PSADT) (from 15.9 to 42.5 months; P= 0.0271) [18,19], a phase II trial was conducted in men with newly diagnosed localized intermediate and high-risk prostate cancer receiving radiation and androgen deprivation therapy (ADT). Adv-tk was studied in this setting because both radiation and ADT have been shown to have the potential to enhance anti-tumor immune responses [20][21][22][23][24][25][26]. In this phase II trial men receiving radiation, ADT and Adv-tk showed sustained T cell immune responses at a year.…”
Section: Prostatakmentioning
confidence: 96%
“…ADT has been found to potentiate an immune response through a number of mechanisms including increasing T cell infiltration into the prostate, increasing thymic production of naïve T cells, and diminishing immune tolerance [23][24][25][26]. Preclinical studies of enzalutamide and abiraterone have found that these agents enhance immune responses and lead to improved outcomes in combination with immunotherapy [69,70].…”
Section: Future Directionsmentioning
confidence: 97%
“…Treatment of the patients with 3 to 4 months of an LHRH-a immediately prior to sipuleucel-T treatment may have contributed to the observed prolongation of PSADT in the treatment arm. Recent studies suggest a potential synergy between androgen deprivation and immunotherapy (34). Specifically, castration or androgen deprivation therapy has been shown to induce Time from randomization (months) 48 60…”
Section: Discussionmentioning
confidence: 99%